The Effect Of Using Two Strategies for Individual and Team Work On Learning Artistic Performance In 5000m Walking Event - saber , ameal (Journal of Physical Education, 2023)
The Aim of study to know to Correlations between of the Running the destines (100, 400, 1500) m & in same of Biochemical Markers (CPK, LDH. Ca, Mg). In it study using Correlation research. And choose the subjects from the (30) Athletes and divide it three groups at the amateur A Running. The Conclusions of research are deferens in Correlations between of the Running the destines (100, 400, 1500) m & in same of Biochemical Markers (CPK, LDH. Ca, Mg). We know that err in the training